Penerapan Model Pembelajaran Quiz Team Untuk Meningkatkan Motivasi Dan Hasil Belajar Materi Pemerintah Kabupaten Dan Kota Pada Siswa Kelas IV SD 4 Kaliwungu - Anik Sulistyowati (Universitas Muria Kudus, 2018)
The data obtained during the observations were carried out for students and 4th grade students of SD 4 Kaliwungu Kudus district and city education material was still low, some helped students by 35% and completeness of student learning outcomes by 29%. This is caused by the teacher still using conventional methods, students are interested in low learning. Based on the description above, the authors are interested in clearing up the research on